2020
DOI: 10.1080/01652176.2020.1803512
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous antegrade pyelography for suspected ureteral obstruction in 6 pet guinea pigs (Cavia porcellus)

Abstract: Objectives: To describe the feasibility and safety of ultrasound-guided percutaneous antegrade pyelography (US-PAP) in pet guinea pigs (Cavia porcellus) with suspected ureteral obstruction. Materials and methods: Six adult pet guinea pigs (4 females and 2 males, all intact) were evaluated for suspected ureteral obstruction. The mean weight of the guinea pigs was 0.8 ± 0.25 kg (range 0.4-1.1 kg), and mean age was 4.07 ± 1.63 years (range 2-7 years). All animals were free from comorbid diseases, had clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Momzudar et al discovered that obesity was the most prevalent maternal comorbidity and that maternal comorbidities as a whole were demonstrated to be a significant independent predictor of diagnostic discrepancy. Therefore, it is suggested that these patients should undergo repeat ultrasound exams, with more experienced sonographers and undergo a longer examination time when imaging is not ideal [27].…”
Section: Discussionmentioning
confidence: 99%
“…Momzudar et al discovered that obesity was the most prevalent maternal comorbidity and that maternal comorbidities as a whole were demonstrated to be a significant independent predictor of diagnostic discrepancy. Therefore, it is suggested that these patients should undergo repeat ultrasound exams, with more experienced sonographers and undergo a longer examination time when imaging is not ideal [27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a contrast study is necessary to confirm the location of the leakage and to plan surgical therapy [ 12 ]. Nevertheless, an intravenous contrast agent is a nephrotoxic risk factor in patients whose renal function is already compromised [ 13 , 14 ]. In this study, the cat was presented in a shock condition (hypothermia, dehydration, prolonged capillary refill time, severe azotemia), rendering contrast radiography and excretory urography contraindicated [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of gonadal shields in patients. Ray Direction : Directed perpendicular to the center point of the os calcaneus [25]. Cassette : 18 cm x 24 cm.…”
Section: Lateral Projectionmentioning
confidence: 99%